Excellent work ethics and moral values in public administration: a comparative appraisal - Mohamad Yunus, Mohamad Ismail (POLIS DIRAJA MALAYSIA, 2010)
The key contribution of this article to the public officials in their conduct of public affairs is to recommend such moral principles as: consistency, impartiality, responsibility, accountability, trustworthiness and maintenance of a high degree of ethical and moral standards in the public sector. Hence the mission is to develop more who are well informed in the light of the qualities the community should expect to find in them as public servants with unquestionable integrity, who preserve high ethical standards under all circumstances. According to Cloete1, public functionaries should always be informed of the rules which apply in the work situation and which govern their conduct. To discover the nature of ethical life with the moral principles central to good public administration is an intellectual task similar to the discovery of mathematical truths. Just as untrained people cannot know the latter, though they may accidentally hit upon the correct answer, so the former cannot be known either. Only as a result of the right kind of training does one have the capacity to know what is moral. Only if a public official has knowledge of objective moral principles can he or she be assured of leading an ethical and moral life. From the discussion it realizes that not only physical fitness is necessary but high intellectual, spiritual, moral and emotional skills are also required and relevant for positions of public servant.